Age and Sex Normalization of Intestinal Permeability Measures for the Improved Assessment of Enteropathy in Infancy and Early Childhood: Results From the MAL-ED Study. Issue 1 (July 2017) - Kosek, Margaret N.; Lee, Gwenyth O.; Guerrant, Richard L.; Haque, Rashidul; Kang, Gagandeep; Ahmed, Tahmeed; Bessong, Pascal; Ali, Asad; Mduma, Estomih; Peñataro Yori, Pablo; Faubion, William A.; Lima, Aldo A.M.; et al.
ABSTRACT: Objectives: The aim of the study was to describe changes in intestinal permeability in early childhood in diverse epidemiologic settings. Methods: In a birth cohort study, the lactulose:mannitol (L:M) test was administered to 1980 children at 4 time points in the first 24 months of life in 8 countries. Data from the Brazil site with an incidence of diarrhea similar to that seen in the United States and no growth faltering was used as an internal study reference to derive age- and sex-specific z scores for mannitol and lactulose recoveries and the L:M ratio. Results: A total of 6602 tests demonstrated mannitol recovery, lactulose recovery, and the L:M ratio were associated with country, sex, and age. There was heterogeneity in the recovery of both probes between sites with mean mannitol recovery ranging for 1.34% to 5.88%, lactulose recovery of 0.19% to 0.58%, and L:M ratios 0.10 to 0.17 in boys of 3 months of age across different sites. We observed strong sex-specific differences in both mannitol and lactulose recovery, with boys having higher recovery of both probes. Alterations in intestinal barrier function increased in most sites from 3 to 9 months of age and plateaued or diminished from 9 to 15 months of age. Conclusions: Alterations in recovery of the probes differ markedly in different epidemiologic contexts in children living in the developing world. The rate of change in the L:M- z ratio was most rapid and consistently disparate from the reference standard in the period between 6 and 9 months of age, suggesting that this is a critical period of physiologic impact of enteropathy in these populations. Abstract : Supplemental Digital Content is available in the text